Prevalence of undernutrition and associated factors among children with congenital heart disease in Africa: a systemic review and meta-analysis - Mequanint Ayehu Akele; Tenagnework Eseyneh Dagnaw; Molla Getie Mehari; Amare Mebrat Delie; Daniel Sisay W/tsadik; Migbar Sibhat Mekonnen; Tamalew Alemie Tegegn; Dires Birhanu Mihretie; Kassa Genetu Alem (Journal of Translational Medicine)
Abstract Background Undernutrition is a major public health issue in children with congenital heart disease in Africa. In this continent, the degree of undernutrition also varies from country to country. Therefore, summarizing data concerning undernutrition in children with congenital heart disease is essential to refine treatment guidelines and policies. This meta-analysis aims to deliver pooled data concerning undernutrition among African children with congenital heart disease. Methods In this review, relevant studies were searched via PubMed/MEDLINE online, Science Direct, Hinari, Web of Science, CINHAL, EMBASE, WHO database, Google, and Google Scholar. To conduct this review, PRISMA guidelines were used. STATA 17 was used to estimate the pooled prevalence of undernutrition in children. A random effect meta-analysis model was used to conduct this meta-analysis. The heterogeneity of the studies was evaluated by the I2 test. Publication bias was assessed via funnel plots supplemented with Egger's weighted regression test. Finally, for all analyses, p < 0.05 was considered statistically significant. Result In this review, a total of 5898 studies were found. Among these, 5878 were excluded using PRISMA, and the remaining 20 studies were included in the final analysis. The prevalence of undernutrition, underweight, wasting, and stunting in children with congenital heart disease was 65.14% (95% CI 51.32–78.95, I2 = 97.4%, p = 0.0001), 45.76% (95% CI 35.83–55.69, I2 = 96.7, p < 0.0001), 39.37% (95% CI 29.55–49.19, I2 = 97.4, p < 0.0001), and 39.38% (95% CI 33.02–45.72, I2 = 92.4%, p < 0.0001), respectively. Anemia (OR = 4.5, 95% CI 1.60–12.68), CHF (OR = 5.98, 95% CI 3.09–11.57), pulmonary hypertension (OR = 2.76, 95% CI 1.89–4.04), and age (OR = 2.78, 95% CI 1.79–4.31) were associated with undernutrition in children with CHD. Conclusion In this meta-analysis, the pooled prevalence of undernutrition and its indicators in children with CHD were high. As a result, there is still a need to improve early screening and treatment of undernutrition in children with congenital heart disease concomitant with early screening and treatment of congenital heart disease and its common complications in Africa.